CONCEPT OF LEAK TIGHTNESS MONITORING AT UNDERGROUND GAS STORAGE - Horáková, Markéta; Ryba, Jakub; Roček, Erik (GeoScience Engineering, 2019)
The most important part of the operation of each underground gas storage facility is the implementation of a regular monitoring system for leak tightness monitoring. This article deals with the design of a proposal leak tightness monitoring concept in underground gas storage in porous reservoirs (depleted gas/oil reservoirs, aquifer reservoirs). This concept interconnects all commonly used and established leak tightness monitoring methodologies and evaluates them in time with a comparison with historical results with reference to possible solutions or implementation of remedial measures. Keywords: underground gas storage, leak tightness, well integrity http://doi.org/10.35180/gse-2019-0012